Inclusion of persons with disabilities in mainstream employment: is it really all about the money? A case study of four large companies in Norway and Sweden. Issue 2 (7th February 2017) - Kuznetsova, Yuliya; Yalcin, Betul
Abstract: This study investigates how large companies respond to public policy measures to ensure the inclusion of persons with disabilities in mainstream employment based on a case study of four companies in Norway and Sweden. The qualitative interviews, which were conducted with company managers, government representatives in Norway, and non-governmental organisations in Sweden, revealed three overarching themes: (1) 'legitimacy', (2) 'financial interests' and (3) 'non-financial support'. The results indicate a more proactive response from the Swedish companies, especially regarding persons with intellectual and learning difficulties. The Norwegian companies reveal a high commitment to their own employees. These findings cannot be explained solely using neo-institutional theory, which holds that organisations demonstrate 'conformity with powerful institutional myths to strengthen support and secure survival'. The results indicate that inclusive targeted corporate policies and programmes, advisory support, and the agency and value choices of the management might matter more.